(untitled) (Medico Legal Update, 2021)
Background: Study in correlation between Senile cataract and Serum 25-Hydroxyl Vitamin D Insufficiency. Mean Value of vitamin -D less than 10ng/ml seen in group-1 which show severe deficiency. Mean Level of vitamin-D in group-2 15-24 ng/ml which show mild to moderate deficiency. There was a statistically significant difference in both groups.(p value-<0.03) Method: 25 OH D level were examined in 300 patients who had cataract and 280 normal patients of both sex were examined using the technology name as chemiluminescent micro particle immunoassay (CMIA). Conclusion: In normal patients have below the reference levels while a severe insufficiency of 25-OH D levels in cataract patients. These shows the role of 25-OH D deficiency in senilecataract patients.